Ghost-Fluid-Based Sharp Interface Methods for Multi-Material Dynamics: A Review (Communications in Computational Physics, 2023)
The ghost fluid method (GFM) provides a simple way to simulate the interaction of immiscible materials. Especially, the modified GFM (MGFM) and its variants,based on the solutions of multi-material Riemann problems, are capable of faithfullytaking into account the effects of nonlinear wave interaction and material propertynear the interface. Reasonable treatments for ghost fluid states or interface conditionshave been shown to be crucial when applied to various interfacial phenomena involving large discontinuity and strong nonlinearity. These methods, therefore, have greatpotential in engineering applications. In this paper, we review the development ofsuch methods. The methodologies of representative GFM-based algorithms for definition of interface conditions are illustrated and compared to each other. The researchprogresses in design principle and accuracy analysis are briefly described. Some stepsand techniques for multi-dimensional extension are also summarized. In addition, wepresent some progresses in more challenging scientific problems, including a varietyof fluid/solid-fluid/solid interactions with complex physical properties. Of course thechallenges faced by researchers in this field are also discussed.
Keywords: Multi-material flows; sharp-interface method; ghost fluid method; modified ghost fluid method; fluid-solid interaction; multi-material Riemann problem.